Tingkat Kecerdasan Ekologis Siswa Sekolah Menengah Umum di Wilayah Bandung Utara - Muhamad Abdul Azis; Mamat Ruhimat; Bagja Waluya (Syntax Idea)
The North Bandung Area (KBU) has a function as a rainwater catchment area in the Bandung Basin. However, today, KBU has experienced land conversion, especially agricultural land into built-up land. If land conversion in KBU cannot be controlled and continues to experience land use changes, public knowledge about the environment in KBU will be increasingly eroded and cause disharmony between the community and its physical environment. The purpose of this research is to identify the level of ecological intelligence of high school students in KBU. The method used in this research is the survey method and the approach used is quantitative. The location of this research was conducted in 12 State Senior High Schools (SMAN) which are included in the North Bandung Area (KBU). The result of this research: Ecological intelligence of public high school students in KBU in the knowledge aspect falls into the high category (1.50), in the attitude aspect falls into the high category (1.98), the skill aspect falls into the high category (1.86), and the participatory aspect falls into the high category (1.91). In general, the ecological intelligence of students of 12 public high schools in KBU as measured through four indicators is classified as high category (1.81). It is recommended to conduct similar research at different levels and or in private schools.